Managerial Ownership and Financial Analysts' Information Environment. (April 2014) - Han, Sam; Jin, Justin Yiqiang; Kang, Tony; Lobo, Gerald
Abstract Despite the importance of sell‐side financial analysts as information intermediaries in the capital market, little is known about how managerial equity ownership is associated with their information environment. Using Barron, Kim, Lim and Stevens' (1998) framework for measuring the precision of financial analysts' information, we observe that managerial ownership is positively associated with the precision of financial analysts' public (common) and private (idiosyncratic) information, largely consistent with the alignment view of managerial equity ownership. These results are robust to controlling for various economic and statistical factors that might affect the inference.